Psalms of promise celebrating the majesty and faithfulness of God - Beisner, E. Calvin (Phillipsburg, NJ Presbyterian and Reformed, 1994)
Includes bibliographical references.
Keywords: Bible. O.T. Psalms -- criticism, interpretation, etc; God -- biblical teaching